Gender-Related Impact of Sclerostin Antibody on Bone in the Osteogenesis Imperfecta Mouse - Cardinal, Mickaël; Chretien, Antoine; Roels, Thomas; Lafont, Sébastien; Ominsky, Michael S.; Devogelaer, Jean-Pierre; Manicourt, Daniel H.; Behets, Catherine (Frontiers in Genetics, 2021)
Osteogenesis imperfecta (OI), which is most often due to a collagen type 1 gene mutation, is characterized by low bone density and bone fragility. In OI patients, gender-related differences were reported, but data in the literature are not convergent. We previously observed that sclerostin antibody (Scl-Ab), which stimulates osteoblast Wnt pathway via sclerostin inactivation, improved spine and long bone parameters and biomechanical strength in female oim/oim mice, a validated model of human type 3 OI. We wanted to highlight Scl-Ab effect on male oim/oim bones in order to identify a possible distinct therapeutic effect from that observed in females. According to the same protocol as our previous study with female, male Wildtype (Wt) and oim/oim mice received vehicle or Scl-Ab from 5 to 14 weeks of age. Clinimetric and quantitative bone parameters were studied using X-rays, pQCT, microradiography and dynamic histomorphometry and compared to those of females. Contrary to Wt, male oim/oim had significantly lower weight, snout-sacrum length and bone mineral content than females at 4 weeks. No significant difference in these clinimetric parameters was observed at 14 weeks, whereas male oim showed significantly more long bone fractures than females. Scl-Ab improved bone mineral density and bone volume/total volume ratio (BV/TV) of vertebral body in Wt and oim/oim, without significant difference between male and female at 14 weeks. Male vehicle oim/oim had a significantly lower cortical thickness (Ct.Th) and BV/TV of tibial diaphysis than female and showed a higher number of fractures at 14 weeks. Scl-Ab increased midshaft periosteal apposition rate in such a way that tibial Ct.Th of male oim/oim was not significantly different from female one at 14 weeks. The number of fractures was lower in male than female oim/oim after 14 weeks of Scl-Ab treatment but this difference was not significant. Nevertheless, Scl-Ab treated oim/oim male and female mice remained smaller than WT ones. In conclusion, our results highlighted differences between male and female oim/oim at 4 and 14 weeks of age, as well as some male specific answer of cortical bone to sclerostin antibody. These gender-related particularities of oim/oim should be considered when testing experimental treatments.